Determination of neurotoxic agents as markers of common vetch adulteration in lentil by LC-MS/MS - GÖREN, AHMET CEYHAN; Ghasemi, Nesa; SEÇEN, Hasan; YILMAZ, Hasibe; BINICI, Burcu; Goren, AHMET CEYHAN (My University, 2017)
Vicia sativa (common vetch), which contains beta-cyanoalanine (BCA) and c-glutamyl beta-cyanoalanine (cGBCA) is used for adulteration of lentil and have neuro toxic effects on people and animals. Therefore the determination of BCA and gamma GBCA analytes in accurate and reliable manner has high importance for human and animal health. LC-IDMS/MS method has been developed and validated for quantitative analyses of beta-cyanoalanine and C-13 labeled BCA is used as an internal standard in gamma GBCA analysis. In order to validate the method, linearity, recovery, precision (repeatability), intermediate precision, limit of detection, and limit of quantification parameters were investigated. The correlation coefficient was found to be greater than 0.99 for both analytes. The recoveriess were determined as 95.8% for BCA and 97.4% for gamma GBCA. The relative expanded measurement uncertainties of beta-cyanoalanine and gamma-glutamyl-beta-cyanoalanine were obtained as 4.6% and 5.8%, respectively with the coverage factor, k, is 2 and at 95% confidence level. (C) 2016 Elsevier Ltd. All rights reserved.